2020
DOI: 10.1016/j.sjbs.2019.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Diadochokinetic rate in Saudi and Bahraini Arabic speakers: Dialect and the influence of syllable type

Abstract: Arabic is spoken by more than 420 million people worldwide and still there are a limited number of studies on dialects of the Gulf Arabic regions where most selected respondents are male speakers. This study aimed to explore and establish normative data for the Diadochokinetic Rate (DDK) for two dialects (Saudi Arabia’s Najdi and Bahrain’s Bahraini) speakers. Furthermore, it aimed to investigate whether there are differences between the two dialects and whether sex differences are evident. In addition, it inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 33 publications
(49 reference statements)
4
13
0
Order By: Relevance
“…In Greek, the voiceless consonants /p/, /t/ are in free variation and can be produced as aspirated or not by Greek speakers, depending on the phonetic context and the speaker, while the speech sound /k/ shows allophonic variations, that is, the phones [k] and [c] which are in complementary distribution, with their distribution modulated by the vowel following the phoneme /k/ (i.e., /ka/, /ko/, /ku/-not middle/back vowels but /ci/, /ce/-front vowels (Arvaniti, 1999;Bernthal et al, 2017:11). In a recent study, Alshahwan et al (2020) found that Saudi adult speakers produced the monosyllables /ba/, /da/, /ga/ significantly faster than Bahraini adult speakers, thus proposing the establishment of separate norms for each Arabic population. Furthermore, the frequency of separate phonemes, and place of articulation, varies in each language and may affect the speed of production (Ben-David & Icht, 2016).…”
Section: Cross-linguistic Effects On Speech Ddk Ratesmentioning
confidence: 99%
“…In Greek, the voiceless consonants /p/, /t/ are in free variation and can be produced as aspirated or not by Greek speakers, depending on the phonetic context and the speaker, while the speech sound /k/ shows allophonic variations, that is, the phones [k] and [c] which are in complementary distribution, with their distribution modulated by the vowel following the phoneme /k/ (i.e., /ka/, /ko/, /ku/-not middle/back vowels but /ci/, /ce/-front vowels (Arvaniti, 1999;Bernthal et al, 2017:11). In a recent study, Alshahwan et al (2020) found that Saudi adult speakers produced the monosyllables /ba/, /da/, /ga/ significantly faster than Bahraini adult speakers, thus proposing the establishment of separate norms for each Arabic population. Furthermore, the frequency of separate phonemes, and place of articulation, varies in each language and may affect the speed of production (Ben-David & Icht, 2016).…”
Section: Cross-linguistic Effects On Speech Ddk Ratesmentioning
confidence: 99%
“…Age and language are two variable affecting diadochokinetic activity significantly (Kent, 2021). Studies on diadochokinetic performance have been conducted in some languages other than English like Arabic (Alshahwan et al, 2020); Hebrew (Ben-David & Icht, 2017); Thai (Prathanee et al, 2003a); Malayan (Yang et al, 2011); and Greek (Tafiadis et al, 2021). Those researches revealed diadochinetic data on syllable and word levels.…”
Section: Introductionmentioning
confidence: 99%
“…The search on data on DDK quantification at single and double syllables and word level is very important (Alshahwan et al, 2020). In addition to providing syllable-and word-based information, the fulfilment of information on DKK in syllables with voiced and voiceless consonant becomes important.…”
Section: Introductionmentioning
confidence: 99%
“…Word and material choices in ethnocultural-based DDK activity play an important role in handling speech disorder related to motor-speech process. Studies have been conducted to see DDK across languages (Alshahwan et al, 2020;Icht & Ben-David, 2014), but none to see DDK ability in Indonesian language speakers.…”
Section: Introductionmentioning
confidence: 99%